Does artificial feeding impact neonate growth rates in a large free-ranging mammal?. Issue 3 (22nd March 2023) - Griffin, Laura L.; Haigh, Amy; Amin, Bawan; Faull, Jane; Corcoran, Fiachra; Baker-Horne, Connie; Ciuti, Simone
Abstract : Variation and disparity in resource access between individuals in an animal population within human-dominated landscapes require attention as artificial selection processes may be at work. Independent, recreational human–wildlife feeding interactions constitute an increasingly prevalent, yet understudied, food resource for birds and mammals living in our cities. However, only a limited number of risk-taking individuals may access it. Using urban fallow deer as our model species, we hypothesized that if these interactions result in positive effects for the engaging individual, e.g. increased milk quality and yield, then this would result in the increased growth rates of their offspring. Alternatively, if these individuals were prioritizing investing time in engagement with humans, resulting in decreased maternal care, then this would result in slower growth rates in their offspring. We found that the offspring of those females that regularly interacted with humans displayed significantly faster growth rates than their risk-adverse counterparts. This advantage for fearless mothers in terms of boosted neonatal growth rates could be mirrored in birds accessing garden feeders, seagulls or pigeons utilizing urban resources, or seals approaching city harbours. Here, we add a new piece to the complex puzzle of how humans are impacting wildlife living within human-dominated landscapes.